The Effectiveness of Ice Breaking to Increase Student Motivation in Learning Physical Education, Sport, and Health at Teluk Dalam 3 Elementary School, Banjarmasin - Dede Adi Jaya; Herita Warni; Nurdiansyah (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Learning motivation is an important factor in successful learning, especially in Physical Education, Sports and Health (PESH) subjects that require active participation of students. One method that can be used to increase student learning motivation is ice breaking. This study aims to analyze the effectiveness of ice breaking in increasing student motivation in learning PESH at Teluk Dalam 3 Elementary School Banjarmasin. The research method used was a survey involving 32 respondents. Data was obtained through a questionnaire that measured students’ perceptions of the effect of ice breaking in PESH learning. The results showed that the majority of students gave a positive response to the application of ice breaking. As many as 78.1% of students felt more motivated after participating in ice breaking, 87.5% of students felt that the learning atmosphere was more interactive and fun, and 81.3% of students stated that ice breaking helped improve focus and concentration during learning. The study concludes that ice breaking is an effective pedagogical strategy that should be continuously implemented and varied according to student characteristics and needs. This method not only enhances learning motivation but also creates a more interactive, enjoyable, and conducive learning environment, ultimately supporting better academic outcomes in physical education at the elementary school level.